The handbook of group research and practice - Wheelan, Susan A. (SAGE Publications, 2005)
"The Handbook of Group Research and Practice emphasizes the connections among basic research and theory, applied research, and group practice to demonstrate how theory and research translate into methods for working with groups. It is an excellent resource for students, academics, and practitioners in the fields of psychotherapy, psychology, sociology, management, communications, social work, education, and science and technology."--